(untitled) (Research, Society and Development, 2021)
The objective was, therefore, to analyze the experience of mothers who lost children. It is an empirical study with nine mothers who participate in the group Mother of Pietà. The narratives were analyzed based on the categories of analysis: The report of death; The experience of losing a child, the most evident feelings after the loss; Family dynamics before and after the loss; Moments and memories; The time needed for emotional response; 6. Main physical and emotional changes. It was identified that family support, spirituality, the continuity of the bond with the deceased child, interaction and the development of actions through the group Mother of Pietà were fundamental in the reconstruction of the meaning of life. It is important to emphasize that the type of death and the time elapsed are essential in understanding the coping. Based on the narratives of bereaved mothers, it was possible to verify that grief is experienced differently, allowing each mother to develop her relationship with the loss in a unique way.